Higher Impulsivity As a Distinctive Trait of Severe Cocaine Addiction among Individuals Treated for Cocaine or Alcohol Use Disorders - García-Marchena, Nuria; Ladrón de Guevara-Miranda, David; Pedraz, María; Araos, Pedro Fernando; Rubio, Gabriel; Ruiz, Juan Jesús; Pavón, Francisco Javier; Serrano, Antonia; Castilla-Ortega, Estela; Santín, Luis J.; Rodríguez de Fonseca, Fernando (Frontiers in Psychiatry, 2018)
Despite alcohol being the most often used addictive substance among addicted patients, use of other substances such as cocaine has increased over recent years, and the combination of both drugs aggravates health impairment and complicates clinical assessment. The aim of the present study is to identify and characterize heterogeneous subgroups of cocaine- and alcohol-addicted patients with common characteristics based on substance use disorders, psychiatric comorbidity and impulsivity. A total of 214 subjects with cocaine and/or alcohol use disorders were recruited from outpatient treatment programs and clinically assessed. A latent class analysis was used to establish phenotypic categories according to diagnosis of cocaine and alcohol use disorders, mental disorders, and impulsivity scores. Relevant variables were examined in the latent classes using correlation and analyses of variance and covariance. Four latent classes were identified: Class 1 (45.3%) formed by alcohol-dependent patients exhibiting lifetime mood disorder diagnosis and mild impulsivity; Class 2 (14%) formed mainly by lifetime cocaine use disorder patients with low probability of comorbid mental disorders and mild impulsivity; Class 3 (10.7%) formed by cocaine use disorder patients with elevated probability to course with lifetime anxiety, early-onset and personality disorders, and greater impulsivity scores; and Class 4 (29.9%) formed mainly by patients with alcohol and cocaine use disorders, with elevated probability in early-onset and personality disorders and elevated impulsivity. Furthermore, there were significant differences among classes in terms of DSM-IV-TR criteria for abuse and dependence: Class 3 showed more criteria for cocaine use disorders than other classes, while Class 1 and 4 showed more criteria for alcohol use disorders. Cocaine- and alcohol-addicted patients who were grouped according to diagnosis of substance use disorders, psychiatric comorbidity and impulsivity show different clinical and socio-demographic variables. Whereas mood and anxiety disorders are more prevalent in alcohol-addicted patients, personality disorders are associated with cocaine use disorders and diagnosis of comorbid substance use disorders. Notably, increased impulsivity is a distinctive characteristic of patients with severe cocaine use disorder and comorbid personality disorders. Psychiatric disorders and impulsivity should be considered for improving the stratification of addicted patients with shared characteristics in order to select more appropiate treatments.